On the right track: Does senior high school tracking matter? - Gorospe, Joanne D.; Joaquin, Joliwar M. (Technium Social Sciences Journal, 2022)
Instructional effects of tracking could have serious consequences for students and important implications for educational policy and practice. This study aimed to find out whether tracking during senior high school matters when choosing a program in college. For this purpose, descriptive design was employed to address the problem of the study. On the other hand, due to some problems of the study which cannot be addressed quantitatively, there was an element of qualitative method that was used in the conduct of the study. The findings revealed that the majority of the students came from the Academic Track, specifically from the General Academic Strand. Students have a very satisfactory performance but they vary in their performance when grouped according to track/strand. The students from the non-HUMMS strand believe that subject alignment to teacher education and teacher preparation are the problems that they encountered when they are already in the teacher education program. The students agreed that tracking is no longer a factor in choosing a program in college.